Effect of Different ET-Based Irrigation Scheduling on Grain Yield and Water Use Efficiency of Drip Irrigated Maize - Dejan Simić; Borivoj Pejić; Goran Bekavac; Ksenija Mačkić; Bojan Vojnov; Ivana Bajić; Vladimir Sikora (Agriculture, 2023)
The development of irrigation schedules based on water balance implies a study of daily plant water requirements. A properly selected irrigation method is also of most importance. The objective of this study was to find out how surface drip irrigation (SDI) and shallow subsurface drip irrigation (SSDI), as well as different ET-based irrigation scheduling for maize (reference evapotranspiration (ETo), pan evaporation (Eo), and local climatic coefficients (lc)), affect grain yield, water use efficiency (WUE), and yield response factor (Ky) of maize. The field experiments were conducted in Vojvodina, a northern part of the Republic of Serbia, on the calcareous gleyic chernozem soil, using a complete block design in three replicates in 2019–2021. The water balance method was used for irrigation scheduling. The nonirrigated treatment was used as a control. The yield in irrigation conditions was statistically higher as compared with the nonirrigated control variant. Concerning the tested parameters, especially the maize yield, reference evapotranspiration (ETo) should be recommended as the most acceptable method for assessing maize evapotranspiration. Preference should be given to SSDI compared to SDI because the installation of laterals can be performed together with the sowing, which can ensure the uniform and timely emergence of plants. Based on the Ky coefficient of 0.71, it can be concluded that maize is moderately tolerant to water stress in Vojvodina’s temperate climate. The results can contribute to precise planning and efficient irrigation of maize in the region, implying high and stable yields.